Prioritization of Post-Myocardial Infarction Heart Failure Targets Using Large-Scale Plasma Proteomics and Genome-Wide Single-Cardiac Cell Transcriptomics - Chan, Mark Y (LIPPINCOTT WILLIAMS & WILKINS, 2021)
Scientific Sessions of the American-Heart-Association